Chlorogenic acid stabilized nanostructured lipid carriers (NLC) of atorvastatin: formulation, design and in vivo evaluation. (1st February 2016) - Khan, Saba; Baboota, Sanjula; Ali, Javed; Narang, R. S.; Narang, Jasjeet K.
Abstract: The present work was aimed at developing an optimized oral nanostructured lipid carrier (NLC) formulation of poorly soluble atorvastatin Ca (AT Ca) and assessing its in vitro release, oral bioavailability and pharmacodynamic activity. In this study, chlorogenic acid, a novel excipient having synergistic cholesterol lowering activity was utilized and explored in NLC formulation development . The drug-loaded NLC formulations were prepared using a high pressure homogenization technique and optimized by the Box-Behnken statistical design using the Design-Expert software. The optimized NLC formulation was composed of oleic acid and stearic acid as lipid phase (0.9% w/v), poloxamer 188 as surfactant (1% w/v) and chlorogenic acid (0.05% w/v). The mean particle size, polydispersity index (PDI) and % drug entrapment efficiency of optimized NLC were 203.56 ± 8.57 nm, 0.27 ± 0.028 and 83.66 ± 5.69, respectively. In vitro release studies showed that the release of drug from optimized NLC formulations were markedly enhanced as compared to solid lipid nanoparticles (SLN) and drug suspension. The plasma concentration time profile of AT Ca in rats showed 3.08- and 4.89-fold increase in relative bioavailability of developed NLC with respect to marketed preparation (ATORVA® tablet) and drug suspension, respectively. Pharmacodynamic study suggested highly significant ( **p <  0.01) reduction in the cholesterol and triglyceride values by NLC in comparison with ATORVA® tablet. Therefore, the results of in vivo studies demonstrated promising prospects for successful oral delivery of AT Ca by means of its chlorogenic acid integrated NLC.